2020
DOI: 10.1155/2020/9437365
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Content of Salt Use after Years of Universal Iodization Policy and Knowledge on Iodized Salt among Households in the Sissala East Municipality in Upper West Region of Ghana

Abstract: Background. Iodine deficiency is a global public health concern as it leads to inadequate production of thyroid hormone in the body, causing too many destructive consequences on the roles and functions of different human organs and muscles including brain growth and can manifest into many damaging effects such as intestinal cerebral impedance, cancer of intestine, breast disorders, and physical deformities like goitre and cretinism to one’s body. Despite all these negative effects, there are several important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Proper storage of salt will maintain the iodine content in salt. Iodized salt lowers its iodine content if it is not stored under proper conditions such as closed plastic bags, sealed waterproof materials, or closed containers [24]. From this fact, we found that the iodine content of salt was maintained so that there was no correlation between the use of iodized salt and the incidence of stunting.…”
Section: Relationship Between the Use Of Iodized Salt And The Inciden...mentioning
confidence: 85%
See 1 more Smart Citation
“…Proper storage of salt will maintain the iodine content in salt. Iodized salt lowers its iodine content if it is not stored under proper conditions such as closed plastic bags, sealed waterproof materials, or closed containers [24]. From this fact, we found that the iodine content of salt was maintained so that there was no correlation between the use of iodized salt and the incidence of stunting.…”
Section: Relationship Between the Use Of Iodized Salt And The Inciden...mentioning
confidence: 85%
“…Proper storage of salt will maintain the quality of iodine in salt. Iodized salt reduces its iodine content if not stored under proper conditions [24]. The use of iodized salt and proper storage at the household level also need to be considered to avoid IDD in children.…”
Section: Relationship Between Thyroid Gland Palpation With Stunting I...mentioning
confidence: 99%
“…Furthermore, a study on the concentration of salt in households compared to retail stores in Ethiopia reported that inappropriate practices in traders such as exposing iodised salt to sunlight were associated with ethnicity, resulting in loss of iodine in salt (31) . On the other hand, Appiah et al reported that in the Ghanaian population, ethnicity was associated with having good knowledge of the benefits of iodised salt and the dangers associated with iodine deficiency at the household level, and having such knowledge was associated with the increased use of iodised salt (32) . The results of these studies indicate the variability of iodised salt consumption according to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…9 This intervention is widespread, as 68% of households have access to iodized salt. 10 USI is an effective way of delivering iodine to individuals and in term, improving cognition in populations exposed to iodine deficiency. 10,11 USI is also affordable, with annual costs of salt iodization estimated at USD 0.02-0.05 per child, while the costs to prevent child death is estimated at USD 1000.…”
Section: Introductionmentioning
confidence: 99%
“…10 USI is an effective way of delivering iodine to individuals and in term, improving cognition in populations exposed to iodine deficiency. 10,11 USI is also affordable, with annual costs of salt iodization estimated at USD 0.02-0.05 per child, while the costs to prevent child death is estimated at USD 1000. There are also large gains in per Disability-Adjusted Life Years (DALYs), at USD 34-36.…”
Section: Introductionmentioning
confidence: 99%